Approaches and models development of 2013 Curriculum and Merdeka Curriculum - Fahira Azzahra; Hadi Permana; Lulu Fitriani; Rida Maulida Putri; Suci Wulandari (Universitas Pendidikan Indonesia, 2022)
The approach used in curriculum development has differences in the delivery of education. This article aims to discover the models and approaches used in developing Kurikulum 2013 and Kurikulum Merdeka. The method used is library research. Curriculum development has changed from time to time, changes from various aspects of life, globalization, and changes in increasingly advanced technology. The model used in developing the 2013 curriculum combines the Ralph Tyler and Hilda Taba models. The approach used in developing the 2013 curriculum is a competencies-based curriculum and is thematic-integrative. At the same time, the model used in developing Kurikulum Merdeka uses a technological approach and social reconstruction. The curriculum development model used in Kurikulum Merdeka is The Systematic Action Research Model and Emerging Technical Models, which refer to changes in technology and science. The models and approaches used in developing the 2013 curriculum and Merdeka Curriculum are different. Curriculum development has challenges, so it must be able to adapt to various changes by learning to understand curriculum changes and the purpose of the curriculum.